2003
DOI: 10.1007/s00216-003-2111-y
|View full text |Cite
|
Sign up to set email alerts
|

Label-free screening of bio-molecular interactions

Abstract: The majority of techniques currently employed to interrogate a biomolecular interaction require some type of radio- or enzymatic- or fluorescent-labelling to report the binding event. However, there is an increasing awareness of novel techniques that do not require labelling of the ligand or the receptor, and that allow virtually any complex to be screened with minimal assay development. This review focuses on three major label-free screening platforms: surface plasmon resonance biosensors, acoustic biosensors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
308
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(310 citation statements)
references
References 112 publications
1
308
0
1
Order By: Relevance
“…To prove that cladosporols A and B are bona fide PPARc ligands and to assess their binding affinity, we employed a surface plasmon resonance (SPR)-based approach [41]. The acquired sensorgrams showed that both compounds interact with the protein (Fig.…”
Section: Cladosporol B Displays a Different Pparc-mediated Transcriptmentioning
confidence: 99%
“…To prove that cladosporols A and B are bona fide PPARc ligands and to assess their binding affinity, we employed a surface plasmon resonance (SPR)-based approach [41]. The acquired sensorgrams showed that both compounds interact with the protein (Fig.…”
Section: Cladosporol B Displays a Different Pparc-mediated Transcriptmentioning
confidence: 99%
“…[3][4][5][6] SPR is attractive owing to several inherent advantages (e.g., labelfree analysis, simplicity, cost-effectiveness, and high sensitivity). [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The SPR resonance angle variation is dependent on various physicochemical processes occurring at the SPR substrate (a thin metal film or a chemically modified metal surface) and/or the substrate/ solution interface.…”
Section: Introductionmentioning
confidence: 99%
“…Surface plasmon resonance (SPR) is one technique amenable to such measurements. SPR is an optical sensor technique that has the advantage of being able to take real-time measurements using low concentrations of unlabeled biologicals [reviewed in Cooper 2003]. …”
Section: (I) Introductionmentioning
confidence: 99%